Conformational investigation of peptides using solid‐state NMR spectroscopy—A study of polymorphism of β‐turn peptides containing diprolines. (26th December 2019) - Yarava, Jayasubba Reddy; Nishiyama, Yusuke; Raghothama, Srinivasarao; Ramanathan, Krishna Venkatachala
Abstract: The construction of complex protein folds relies on the precise conversion of a linear polypeptide chain into a compact 3‐dimensional structure. In this context, study of isolated secondary structural modules containing short stretches of amino acids assumes significance. Additionally, peptides, both natural and synthetic, play a major role as potential drugs. With a view to understand the local conformations adopted by peptides in the solid state, we propose a multinuclear NMR approach utilizing spectra of nuclei in their natural isotopic abundance. Various solid‐state NMR experiments have been utilized for assignment of the spectra. Additionally, the gauge‐including projector augmented‐wave (GIPAW) calculations were used to confirm the assignments. Particularly, the utility of the double‐quantum–single‐quantum correlation experiments is highlighted for the purpose of assignment and for inferring the conformation across the peptide bond. The methodology is illustrated for the case of designed peptides containing diproline residues occurring at the β‐turns for identifying their cis‐trans conformational polymorphism. The proposed method promises to be of use in the study of conformations of small‐ to medium‐sized peptides such as antimicrobial peptides and in the study of polymorphism leading to applications in drug development protocols. Abstract : A solid‐state NMR study has been carried out to determine the conformational polymorphism of three designed β‐turn peptides containing diproline segments. For this study, a set of robust solid‐state NMR experiments were used to assign the resonances and also to elucidate the structural features of the peptides at their natural isotopic abundance.